2007
DOI: 10.1002/jcb.21345
|View full text |Cite
|
Sign up to set email alerts
|

Functional three‐dimensional HepG2 aggregate cultures generated from an ultrasound trap: Comparison with HepG2 spheroids

Abstract: Three-dimensional culture systems are an ideal in vitro model being capable of sustaining cell functionalities in a manner that resembles the in vivo conditions. In the present study, we developed an ultrasound trap-based technique to rapidly produce HepG2 hepatocarcinoma cell aggregates within 30 min. Enhanced junctional F-actin was observed at the points of cell-cell contact throughout the aggregates. HepG2 aggregates prepared by the ultrasound trap can be maintained in culture on a P-HEMA-coated surface for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 39 publications
2
61
0
1
Order By: Relevance
“…Studies have shown that acoustic trapping of biological cells does not affect the viability of the cells [194][195][196]. Acoustic trapping has been used to culture yeast cells [195], study the effect on inherent agglomeration for in vitro cell-cell interaction studies such as cell adhesion dynamics [196][197][198], long-term culturing [199], and investigation of cell viability and proliferation such as for Hep2G cultures in alginate-gel [200]. Successful acoustical trapping of microparticles has been shown in a flow chamber under environmental control, while Raman spectroscopy was used to detect, distinguish and monitor the chemical reactions in real time [201].…”
Section: Acoustic Manipulationmentioning
confidence: 99%
“…Studies have shown that acoustic trapping of biological cells does not affect the viability of the cells [194][195][196]. Acoustic trapping has been used to culture yeast cells [195], study the effect on inherent agglomeration for in vitro cell-cell interaction studies such as cell adhesion dynamics [196][197][198], long-term culturing [199], and investigation of cell viability and proliferation such as for Hep2G cultures in alginate-gel [200]. Successful acoustical trapping of microparticles has been shown in a flow chamber under environmental control, while Raman spectroscopy was used to detect, distinguish and monitor the chemical reactions in real time [201].…”
Section: Acoustic Manipulationmentioning
confidence: 99%
“…Working without scaffolds, Liu et al [90] formed aggregates of a hepatocyte cell line within an ultrasonic trap, using the ultrasound to accelerate the aggregate formation and to modify their geometry during the initial 30 minutes of their formation. The cells were then maintained in culture in the absence of ultrasound for up to three weeks and shown to have similar functional characteristics to hepatocyte spheroids prepared using gyrotation culture techniques.…”
Section: Assembly and Tissue Engineeringmentioning
confidence: 99%
“…External forces such as dielectrophoresis (35), magnetic fields (36) and ultrasound trap (37,38) were used to enhance cell aggregation and spheroid formation from single cells although specialized equipment is necessary in spheroid formation of the cells. Spheroid formation of HepG2 adhered on a PHEMA-coated surface and encapsulated in alginate capsules was formed within 30 and 5 min, respectively, by the ultrasound trap with good liver-specific functions (37).…”
Section: External Forcesmentioning
confidence: 99%
“…Spheroid formation of HepG2 adhered on a PHEMA-coated surface and encapsulated in alginate capsules was formed within 30 and 5 min, respectively, by the ultrasound trap with good liver-specific functions (37).…”
Section: External Forcesmentioning
confidence: 99%